Guidelines on Energy conserving design of buildings ([Place of publication not identifed] : Department of Energy, 2007)
This document, Guidelines on Energy Conserving Design of Buildings, addresses the need to provide energy efficiency guidelines in the design and construction of buildings in the Philippines.
1. Purpose -- 2. Application and exemption -- 3. Lighting -- 4. Electric power and distribution -- 5. Overall thermal transfer value (OTTV) of building envelope -- 6. Air conditioning and ventilating system -- 7. Steam and hot water systems -- Tables -- Figures -- Appendix
Keywords: CONSERVATION